Kedudukan Akta Hibah dalam Sengketa Kepemilikan Hak Atas Tanah - Hadiyanti, Anisa Rahma; Safa’at, Rachmad; Anshari, Tunggul (University of Jember, 2017)
On each social life will find a difference between behaviour with the law of norms. The discrepancy could cause dispute or tensions between each other that possibly also can happen in the family. The problems often arising during family Is the transition towards treasure in the form of grants from parents to their children. The settlement if there is a standoff over an object of the grant is forced to settle in a court. The Giving in a form of grant was conducted using an authentic deed as has been arranged in article 1682 Indonesian Civil Code. Public officials who given by statute an authority to make the deed of grants is land deed official. Related which for making such deed to as a basis for registration change as a result of a legal action the land. Related to the emergence of signs of a dispute over ownership under the grants, so In this case, every judge as milestone law enforcement have an interpretation of the difference against the rule of law in dispute resolution on the judicial process. In short, there is contradiction a norm between what has been decided by judges with the provision of article 1686 Indonesian Civil Code which the results of the uncertainty laws implementation of the article. Keywords: Deed, Grant, Property Rights, Land Rights